Blame and responsibility in the context of youth produced sexual imagery: The role of teacher empathy and rape myth acceptance. (July 2021) - Sciacca, Beatrice; Mazzone, Angela; O'Higgins Norman, James; Foody, Mairéad
Abstract: This study examined Pre-Service Teachers' (PSTs; N = 92; 75% women, 25% men) tendency to blame students or to feel responsibility when confronted with different vignettes of the sharing of youth produced sexual images. Self-report measures of empathy and rape myth acceptance were collected. Findings showed that PSTs felt more responsible for girl targets depending on the vignette type. Moreover, they blamed the target more in the attention seeking vignette compared to other vignette types. Finally, PSTs who tended to blame the target showed lower levels of empathic concern and higher levels of rape myth acceptance. Implications for teaching education are discussed. Highlights: Teachers felt more responsible when confronted with the non-consensual sharing of girls' semi-nude pictures. Teachers tended to blame the person whose semi-nude pictures were shared in an attention seeking vignette. Lower empathy and higher rape myth acceptance were related to teachers' attribution of blame.